2012
DOI: 10.1016/j.radmeas.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel disk-type X-ray area imaging detector using radiophotoluminescence in silver-activated phosphate glass

Abstract: We report a novel two-and three-dimensional (2-D, 3-D) imaging detector based on the radiophotoluminescence (RPL) phenomenon in silver-activated phosphate glass (PG:Ag) and evaluate its dosimetric characteristics. A compact disk-type PG:Ag detector with a diameter of 80 mm was rotated at a rate of 400 rpm to read out the accumulated dose information and then remove the images for reuse. After X-ray exposure, three RPL dosimeter processes, i.e., preheating, reading, and erasing, were carried out with only a UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
(20 reference statements)
0
23
0
1
Order By: Relevance
“…However, in the present study, the resolution is limited by the readout system utilised for the RPL and PL detectors. Nevertheless, the dose distribution images obtained for the Ag-doped glass detector were reconstructed with a spatial resolution of ~1 μm and a sensitivity of 1 mGy using the prototype reading system [12]. In contrast, in the case of the BaFBr:Eu 2+ detector, which consists of a plastic plate coated with fine PSL crystals (~5 μm), BaFBr:Eu 2+ , 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 11 combined in an organic binder, the spatial resolution (typically, ~25 μm) of the BaFBr:Eu 2+ detector is expected to be inferior to that of the other two detectors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, the resolution is limited by the readout system utilised for the RPL and PL detectors. Nevertheless, the dose distribution images obtained for the Ag-doped glass detector were reconstructed with a spatial resolution of ~1 μm and a sensitivity of 1 mGy using the prototype reading system [12]. In contrast, in the case of the BaFBr:Eu 2+ detector, which consists of a plastic plate coated with fine PSL crystals (~5 μm), BaFBr:Eu 2+ , 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 11 combined in an organic binder, the spatial resolution (typically, ~25 μm) of the BaFBr:Eu 2+ detector is expected to be inferior to that of the other two detectors.…”
mentioning
confidence: 99%
“…To correct the over-response in the low-energy range, Manninen et al [23] reported that a filter composed of tin (Sn) is useful for energy compensation in the diagnostic energy range (50-125 keV), while the filter is not required in the radiation therapy energy range (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) MeV) when using commercially available GD-352M and GD-302M (Asahi Techno Glass Corporation) type glasses based on the RPL phenomena.…”
mentioning
confidence: 99%
“…Though not directly related to silver nanoclusters, an interesting example of the use of silver-doped glasses in sensoristics is the possibility of using silver for creating also optical planar waveguides for chemical sensors [21], while other application fields of silver nanoclusterdoped glass [77] include biosensors (see for example Ref. [78]), biomedical application [79][80][81][82][83], mostly for antibacterial actions [23][24][84][85][86], solar technologies [87][88], glass colouring [89][90][91][92][93], surface-enhanced Raman scattering [94][95], radiophotoluminescence [96][97][98], glass fibers [99][100].…”
Section: Properties Of Silver-doped Glassesmentioning
confidence: 99%
“…Silver-doped glasses have been synthesized by a variety of methods, many of which are still in use after decades, like for example staining processes [101], but novel techniques -or improvements of known techniques-able to control the silver state within the glass matrix have been found without interruption even throughout the last decades [98,[102][103][104]. Among the first methods used to create nanostructured silver clusters within glasses are ion implantation [105][106][107] and sol-gel techniques [7,[108][109][110][111].…”
Section: Synthesis Of the Silver-doped Glassesmentioning
confidence: 99%
“…Recently, a novel disk-type two-dimensional (2D) imaging detector with the aforementioned superior characteristics of radiophotoluminescent dosimeters has been proposed and demonstrated (Kurobori and Nakamura, 2012) for the first time. In addition, a comparative study has been performed of the 2D dose images acquired using Ag-activated phosphate glass based on the orange radiophotoluminescence (RPL) of atomic-scale Agrelated species and those acquired using LiF thin films based on the photoluminescence (PL) of F-aggregate colour centres (CCs) (Montereali et al, 1991), and the performances of the two techniques have been evaluated (Kurobori et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%